Diabetic peripheral neuropathy: advances in diagnosis and strategies for screening and early intervention - Selvarajah, D; Kar, D; Khunti, K; Davies, MJ; Scott, AR; Walker, J; Tesfaye, S (Elsevier, 2019)
Diabetic peripheral neuropathy (DPN) is a common complication of both type 1 and 2 diabetes. It is a leading cause of lower-limb amputation and disabling neuropathic pain. Amputations in patients with diabetes have a devastating effect on quality of life and are associated with an alarmingly low life expectancy (on average only 2 years from the amputation). Amputation also places a substantial financial burden on health-care systems and society in general. With the introduction of national diabetes eye screening programmes, the prevalence of blindness in working-age adults is falling. This is not the case, however, with diabetes related amputations. In this Review, we appraise innovative point-of-care devices that enable the early diagnosis of DPN and assess the evidence for early risk factor-based management strategies to reduce the incidence and slow the progression of DPN. We also propose a framework for screening and early multifactorial interventions as the best prospect for preventing or halting DPN and its devastating sequelae.